Journal of the Proceedings of the Linnean Society of London. Zoology
Accès par la licence nationale : https://revue-sommaire.data.istex.fr/ark:/67375/8Q1-VMG3V372-F de 1856 à 1865
Keywords: Sciences de la vie - Biologie